2011
DOI: 10.1038/ajg.2011.60
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Response and Need for Adalimumab Dose Intensification in Crohn's Disease: A Systematic Review

Abstract: The objective of this study was to review loss of response and need for adalimumab dose intensification in adult and pediatric patients with Crohn's disease. Studies were identified through the electronic databases of MEDLINE and the annual meetings of Digestive Disease Week, of the United European Gastroenterology Week, and of the American College of Gastroenterology and the European Crohn's and Colitis Organization meetings. Studies evaluating loss of efficacy and/or need for dose intensification were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
243
1
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(263 citation statements)
references
References 48 publications
4
243
1
7
Order By: Relevance
“…For ADL, dose intensifying can help to regain clinical response, avoiding the need to switch agents. A meta‐analysis from 2011 has shown that the mean percentage of patients who required dose intensification among primary responders to ADL was 37% and the annual risk was 24.8% per patient‐year 16. Thus, the combination of clinical, biochemical, and endoscopic evaluations and the increasing important role of TDM may help to address the difficulties of LOR to anti‐TNFα, develop strategies to induce and maintain long‐lasting clinical remission, and achieve mucosal healing.…”
Section: Discussionmentioning
confidence: 99%
“…For ADL, dose intensifying can help to regain clinical response, avoiding the need to switch agents. A meta‐analysis from 2011 has shown that the mean percentage of patients who required dose intensification among primary responders to ADL was 37% and the annual risk was 24.8% per patient‐year 16. Thus, the combination of clinical, biochemical, and endoscopic evaluations and the increasing important role of TDM may help to address the difficulties of LOR to anti‐TNFα, develop strategies to induce and maintain long‐lasting clinical remission, and achieve mucosal healing.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk is not distributed evenly, with roughly 2/3 of the patients developing LOR with the fi rst 12 months, and the rest losing response at a signifi cantly slower pace. For ADA, annual LOR incidence of 10%-24% has recently been reported [5,6].…”
Section: Defi Nitions Of Lormentioning
confidence: 99%
“…4 Finally, in the adalimumab group, 16 patients dropped out before the scheduled 54 weeks for clinical worsening or loss of response (n = 8), in spite of which therapy was never intensified. 5,6 All these considerations prevent us to accept the conclusion that 'the efficacy of infliximab and adalimumab is comparable.' As the authors correctly state, 'future prospective double-blind studies in patients matched for clinical variables are required to further assess the efficacy and safety of different anti-TNFs in CD.'…”
Section: Acknowledgementmentioning
confidence: 99%
“…2 In addition, the way biologics were used in this series contradict the assumption that this experience represents their 'real use' in Crohn's disease. [2][3][4][5][6][7] Firstly, cotreatment with immunosuppressors was given in just 16% of cases in the infliximab group. 2,6 Secondly, and surprisingly, only 77% of the infliximab-treated patients were able to complete the induction treatment, mainly due to severe adverse events in eight (18%) patients; this is not generally seen in clinical series.…”
Section: Acknowledgementmentioning
confidence: 99%
See 1 more Smart Citation